2011
DOI: 10.1097/igc.0b013e31820f4ef0
|View full text |Cite
|
Sign up to set email alerts
|

Functional Characterization of a Fluorescent Highly Tumorigenic Ovarian Cancer Line to Test Cellular Therapy in Experimental Models

Abstract: Characterization of SKOV3-AF2 cells revealed that it is more susceptible to PBMC-mediated cytotoxicity than SKOV3-RFP and highly tumorigenic in a xenograph model, and AF-2 tumors express genes that promote aggressive behavior. Collectively, our data suggest that the SKOV3-AF2 subline will be a useful tool to test cellular therapy for the treatment of ovarian cancer utilizing experimental models.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
8
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 23 publications
2
8
0
Order By: Relevance
“…This cytotoxic response was not observed in the absence of IL-2 indicating that IL-2 is necessary for the PBMC to elicit the cytotoxic response [7,10]. In addition, we have shown that IFNa-2b has an inhibitory effect on ovarian cancer cell growth [7]. Therefore, in this study, we proposed to further evaluate cellular therapy using different combinations of cytokines (IL-2 and IFNa-2b) in combination with PBMC in a xenograft murine model of ovarian cancer in order to study their effects in vivo.…”
Section: Introductionmentioning
confidence: 52%
See 4 more Smart Citations
“…This cytotoxic response was not observed in the absence of IL-2 indicating that IL-2 is necessary for the PBMC to elicit the cytotoxic response [7,10]. In addition, we have shown that IFNa-2b has an inhibitory effect on ovarian cancer cell growth [7]. Therefore, in this study, we proposed to further evaluate cellular therapy using different combinations of cytokines (IL-2 and IFNa-2b) in combination with PBMC in a xenograft murine model of ovarian cancer in order to study their effects in vivo.…”
Section: Introductionmentioning
confidence: 52%
“…Cell line culture SKOV3-AF2 cells were derived from SKOV-3 (ATCC, Manassas, VA) cells as recently described by Ingersoll et al [7,8]. Briefly, SKOV3-AF2 cells were derived by first stably transfecting SKOV-3 cells with red-fluorescent protein (SKOV3-RFP), so that the cells could be distinguished from the immune effector cells by fluorescence.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations